2018
DOI: 10.1093/cdn/nzy001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bovine Lactoferrin Reduces Staphylococcus aureus in the Tissues and Modulates the Immune Response in Piglets Systemically Infected with S. aureus

Abstract: BackgroundBovine lactoferrin (bLf) reduces Staphylococcus aureus infection in premature infants and promotes the growth of Bifidobacterium infantis, a predominant infant gut species. We hypothesized that bLf in combination with B. infantis would reduce the severity of systemic S. aureus infection.ObjectiveThe aim was to determine the effects of oral administration of bLf and B. infantis on the course of systemic S. aureus infection.MethodsColostrum-deprived piglets were fed formulas containing 4 g whey/L (CON … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…DNA was isolated from AC contents and feces by combination of the QIAamp Fast DNA Stool Mini Kit (Qiagen, Valencia, CA, USA) with bead beating on the FastPrep-24 System (MP Biomedicals, Carlsbad, CA, USA), as previously described [ 36 ]. The concentration of DNA was measured with a NanoDrop 1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was isolated from AC contents and feces by combination of the QIAamp Fast DNA Stool Mini Kit (Qiagen, Valencia, CA, USA) with bead beating on the FastPrep-24 System (MP Biomedicals, Carlsbad, CA, USA), as previously described [ 36 ]. The concentration of DNA was measured with a NanoDrop 1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the high degree of similarity in anatomy, physiology, immunology, and brain development patterns between pigs and humans, piglets are considered an ideal model for neonatal nutrition research [ 32 , 33 , 34 ]. Piglets have been extensively used as a preclinical model to study the effects of diet and prebiotics on microbiome development [ 20 , 21 , 33 , 34 , 35 , 36 , 37 ]. Therefore, the aim of the study was to evaluate the effect of HMO (2′FL + LNnT), BMOS, and a combination of BMOS and HMO on gut microbiota composition and volatile fatty acid (VFA) concentrations in a piglet model.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from ascending colon (AC, henceforth interchangeably referred to as colonic) contents and feces by the QIAamp Fast DNA Stool Mini Kit (Qiagen, Valencia, CA, USA) in combination with bead beating on the FastPrep-24 System (MP Biomedicals, Carlsbad, CA, USA) as previously described [ 53 ]. DNA concentration was measured with a NanoDrop 1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The bactericidal activity against Gram-positive bacteria appears to be caused by the same residues as with Gram-negative bacteria [ 53 ]. Of interest, a recent study examined the effects of S. aureus bacteremia in piglets pre-treated with dietary bovine Lf [ 54 ] and found that bLf pretreatment effectively reduced S. aureus systemic infection. BLf additionally decreased IL-10 and increased interferon-γ mRNA in these animals, indicating a type 1 T helper (Th1) immune response and, thus, effects on the innate and adaptive immunity of these animals.…”
Section: Direct Anti-microbial Effectsmentioning
confidence: 99%